COMPUTED TOMOGRAPHIC FINDINGS IN CANINE ELBOWS ARTHROSCOPICALLY DIAGNOSED WITH EROSION OF THE MEDIAL COMPARTMENT: AN ANALYTICAL METHOD COMPARISON STUDY. Issue 6 (4th October 2016) - Coppieters, Eva; Van Ryssen, Bernadette; van Bree, Henri; Verhoeven, Geert; Broeckx, Bart; de Bakker, Evelien; Deforce, Dieter; Gielen, Ingrid
Abstract : Medial compartment erosion is an advanced stage of medial coronoid disease, an important cause of elbow lameness in dogs, with treatment and the expected prognosis depending on the extent of the cartilage lesions. The identification of specific computed tomographic (CT) findings might facilitate the nonsurgical diagnosis and add to treatment decision making. Aims of this retrospective, analytical, method comparison study were to describe CT findings in elbows of dogs arthroscopically diagnosed with medial compartment erosion and to compare CT vs. arthroscopic findings. A total of 56 elbows met inclusion criteria. Elbows with focal ( n = 13), diffuse ( n = 11), and complete ( n = 32) erosion were compared. Prevalence findings for CT lesions were as follows: periarticular osteophytosis (100%), abnormal shape of the medial coronoid process of the ulna (96.4%), and subchondral bone defect of the medial part of the humeral condyle (MHC; 96.4%). The three groups significantly differed for presence of medial coronoid process fragmentation, radial head subchondral bone sclerosis, and widening of the humeroulnar joint space. No significant agreement was found between CT and arthroscopy for presence of a subchondral bone defect of the MHC. A significant agreement was found between CT and arthroscopy for presence of fragmentation of the medial coronoid process. However, some of the calcified body/fragment(s) visualized on CT in the region of the medial coronoid process could not be identified via arthroscopy. Findings indicated that an accurate estimation of the extent of the elbow cartilage lesions still requires arthroscopic joint inspection.